The Effect of Using Animation Movies as Learning Media on Students' Listening Skills in Eighth Grade at SMP Negeri 37 Medan - Simatupang, S Uly Menanti; Simarmata, Rina Octavia; Sitorus, Nurhayati (ALACRITY : Journal of Education, 2024)
This research focuses on finding out the effect of the Using Animation Movies on students' listening skill. The aim of this research is to find out whether the using Animation Movies affects students' listening performance. This research was carried out as an applied experimental quantitative research type. The research sample consisted of class VIII students at SMP Negeri 37 Medan. The author took class VIII-A, consisting of 32 students, as an experimental class using the Animation Movies, and class VIII-B, consisting of 32 students, as a control group using the Active Listening Skills Approach. The population of this study was 64 students, consisting of class VIII. The author took two classes as a random sample to see the influence of the Using Animation Movies as a medium for developing students' listening skills. Data is taken by giving a listening test. The test was divided into two tests: a pre-test and a post-test for the experimental and control groups. The average pre-test score in the experimental class was 65,6 and the post-test score was 80. The average pre-test score in the control group was 55,9. and the post-test score was 68,9. This shows that the average score in the experimental group was higher than the control group. The result is t-calculated > t-table with a significance level of p = 0.05 (2,54 > 1.669). The alternative hypothesis (Ha) is accepted, and the null hypothesis (Ho) is rejected. It is recommended that English subject teachers apply the using Animation Movies as an alternative teaching medium to help the listening skills of class VIII students at SMP Negeri 37 Medan.